2014
DOI: 10.3390/ijms150916544
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic DNA Methylation Markers for Prostate Cancer

Abstract: Prostate cancer (PC) is the most commonly diagnosed neoplasm and the third most common cause of cancer-related death amongst men in the Western world. PC is a clinically highly heterogeneous disease, and distinction between aggressive and indolent disease is a major challenge for the management of PC. Currently, no biomarkers or prognostic tools are able to accurately predict tumor progression at the time of diagnosis. Thus, improved biomarkers for PC prognosis are urgently needed. This review focuses on the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
89
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 109 publications
(261 reference statements)
2
89
0
Order By: Relevance
“…41 Additional emerging candidate markers for prognosis were also published. 42,43 Cross validation of these potential prognostic markers in various cohorts will be important to confirm truly useful methylation markers for clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…41 Additional emerging candidate markers for prognosis were also published. 42,43 Cross validation of these potential prognostic markers in various cohorts will be important to confirm truly useful methylation markers for clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylation of PITX2 is associated with poor survival in breast cancer, and it is a prognostic marker of biochemical recurrence in prostate cancer. 74,75 Propero homeobox 1 (PROX1) is a homeobox transcription factor and is associated with breast angiosarcoma and kaposiform hemangioendothelioma. 76 PROX1 is a tumor suppressor gene often hypermethylated in hematological malignancies, sporadic breast cancer, and oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, detection of PCa mainly involves testing of serum prostatespecic antigen (PSA) level. [3][4][5] However, recent studies suggested that PSA is not a specic biomarker of PCa and the diagnostic paradigm suffers from low specicity of PSA. There are further concerns regarding possible over-diagnosis of PCa by PSA in patients with limited potential for disease progression.…”
Section: Introductionmentioning
confidence: 99%